Surgical management of Tympanomastoid Paraganglioma: Experience in BSMMU, Dhaka (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To characterize the clinical presentation, surgical management, and outcomes of a consecutive cases of patients with tympanomastoid paraganglioma (TMP) tumors managed at a single tertiary referral center with 5 years’ experience.Study Design: Retrospective review.Setting: Bangabandhu Sheikh Mujib Medical University, a tertiary referral center in Bangaldesh.Methods: Between November 2014 and May 2019, 10 patients with histologically confirmed TMP tumor underwent surgical treatment. Tumor stage was described using the Sanna modified Fisch and Mattox’s classification system.Results: Distribution of tumors according to modified Fisch and Mattox classification was as follows: type A2 1 case (10%); B1 2 cases (20%), B2 6 cases (60%) and B3 1 case (10%). Class A2 tumour was safely removed via postauricular-transcanal approach. Two patients with Class B1 tumors were operated on through canal wall up mastoidectomy approach. Six patients including five Class B2 and one Class B3 tumors were managed by canal wall down mastoidectomy approach. One Class B2 underwent a subtotal petrosectomy with blind sac closure of the external auditory canal and middle ear obliteration. Gross total tumor removal was achieved in 9 cases (90%). One patient developed facial weakness (HB grade III) after one week of postoperative period which recovered completely by conservative treatment. No recurrence was noted in follow-up period.Conclusion: Early diagnosis of tympanomastoid paragangliomas are very rare because of its benign and slow-growing nature. Clinical differentiation between tympanojugular and tympanomastoid paragangliomas are difficult. Surgery is the recommended primary modality of treatment for tympanomastoid paragangliomas with minimum morbidity and recurrence rate.Bangladesh J Otorhinolaryngol; October 2019; 25(2): 66-75